Phosphorus-based allenes as scaffolds in cycloaddition and cyclization reactions. (1st December 2016) - Swamy, K. C. Kumara; Suresh, R. Rama; Gangadhararao, G.; Anitha, M.
ABSTRACT: In this article, we describe some of our results on the reactions of allenylphosphonates/allenyl phosphine oxides and allenyl diazaphosphole oxides, primarily cycloaddition and cyclization reactions. Depending on the substituents, both the α, β and β, γ -cycloaddition products have been observed. A novel cyclization reaction of a functionalized allenylphosphine oxide with diethylamine leading to 3-diethylamino-4-diphenylphosphinoyl-1-naphthol is reported. Representative compounds have been characterized by X-ray crystallography. GRAPHICAL ABSTRACT: